Dėl lietuvių raštų kalbos kilmės - Zinkevičius, Zigmas (Baltistica, 1977)
On the origin of literary LithuanianThe analysis of old Lithuanian written records shows that in the 16th and 17th centuries there were three variants of literary Lithuanian. One of them had arisen in the then Prussian Dukedom (now the Kaliningrad Region) on the basis of the West High Lithuanian dialect. At the same time two other variants existed in the Grand Duchy of Lithuania. One of them was in use in the bishopric of Samogitia – it had developed from the interdialect of the former Samogitian Dukedom and its ultimate source was the dialect of the lower basin of the Nevėžis (in the East of the Dukedom). The second literary variant of the Grand Duchy of Lithuania was current in the bishopric of Vilnius. It had sprung from the interdialect of the capital – Vilnius, from its koine, which developed from the local East High Lithuanian dialect.The article presents a scheme of the dialect localization of the two latter variants of literary Lithuanian and the names used for them at that time. The Vilnius variant disappeared in the 18th century as a result of the Polonization of the Lithuanian aristocracy. The Samogitian variant lingered on and survived up to the late 19th century. At that time the national Lithuanian movement, fostered by the new inteligentsia from the people, gave it a new impetus putting forward the literary language, traditionally used in the writings of Eastern Prussia, its basis being the West High Lithuanian dialect. Thus, this literary language, adapted to meet new requirements, became Modern Standard Lithuanian.
Keywords: lietuvių raštų kalba; senieji raštai